English Lexical Borrowing in Filipino: Morphophonological Adaptation of English Lexemes and Loanwords - Gessa Mae Sulit; Aiera Beleganio; Honey Grace Candilado; Jessa Lyn Canono; Ruel Bonganciso (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
English has profoundly influenced the Philippine language through the assimilation of source language words into the recipient language. This linguistic exchange, influenced by historical and cultural contacts, has resulted in a notable transformation of linguistic aspects in the Philippines. Over time, English has seamlessly been incorporated into the Filipino language, highlighting a notable process of linguistic exchange. This study specifically delved into the morphological and phonological adaptations of English loanwords in Filipino, examining nuances and shifts in linguistic structure and meaning during the borrowing process through purposive sampling. Qualitative research methods and content analysis were employed, focusing on loanwords extracted from Bob Ong’s novels as a linguistic corpus, delving into the process of incorporating English loanwords into the Filipino language, exploring how this integration instigates a transformation to align with the grammatical and linguistic structure of the target language, and revealing notable morphophonological adaptations and semantic shifts that occur during the borrowing process. Inflections of English lexemes, complemented with Filipino morphemes, were observed, along with modifications to phonological rules, phonotactic constraints, morphemes, and shifts in semantic meaning. The analysis revealed an overall change in the morphophonological structure of phrases and sentences within the corpus. This research underscores the impact of cultural and contextual factors on the adaptation of English loanwords into Filipino, emphasizing specific patterns or structures in the vocabulary borrowing process tailored to the target language. This study contributes valuable insights for linguistic researchers, educators, and language enthusiasts interested in tracing language development and evolution through borrowing and adaptation.